Handbook of the teaching of psychology - Buskist, William; Davis, Stephen F. (Malden, MA ; Oxford, UK : Blackwell Pub., 2006)
The Handbook of the Teaching of Psychology is a state-of-the-art volume that provides readers with comprehensive coverage and analysis of current trends and issues, basic mechanics, and important contextual variables related to effective teaching in psychology. Using concise and targeted chapters, written by leading scholars in the field, the volume explores a myriad of challenges in the teaching of psychology and employs a prescriptive approach to offer strategies and solutions to frequently occurring dilemmas. This book is a lively and informative volume that covers the gamut of current topi.
Introduction to the teaching of psychology -- Preparing for teaching -- Techniques of teaching : approaches and strategies -- Techniques of teaching : special considerations -- Teaching and mentoring diverse students -- Teaching controversial psychology topics -- Classroom management issues -- Evaluating student learning -- Assessment of teaching -- Teaching within the larger context of academic life.
Includes bibliographical references and indexes.
Print version record.
Keywords: Psychology -- Study and teaching; Psychologie -- Étude et enseignement; PSYCHOLOGY -- Education & Training; Psychology -- Study and teaching; Electronic books